Perlindungan Hukum bagi Perempuan Korban KDRT pada Perkara Cerai Gugat - Agil Fatkhurohmah; Muhamad Yunus; Amrullah Hayatudin (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. There are many cases of domestic violence that occur and the majority of victims are women. The women who are victims of domestic violence are the most dominant in carrying out divorce proceedings in the Religious Courts. Divorce contested at the Bandung Religious Court occupying the position of the highest case filed. This study analyzes domestic violence which is processed in the Religious Courts, the forms of legal protection that are carried out when dealing with domestic violence in legislation and the forms of legal protection that are carried out in the Agama Court in Bandung. The approach method used is sociological empirical juridical with the research location in the Bandung Religious Court area. Based on research results, legal protection for victims of domestic violence can be provided by many groups, from advocates, courts, police, prosecutors, communities, health workers, social institutions. The form of legal protection in the Religious Courts is to provide legal assistance from advocates and legal assistance in the form of granting the judge's decision to sue for divorce. Abstrak. Banyaknya kasus kekerasan dalam rumah tangga yang terjadi dan pera korban mayoritas adalah perempuan. Para perempuan korban kekerasan dalam rumah tangga paling dominan melakukan tindakan perceraian di Pengadilan Agama. Cerai gugat di Pengadilan Agama Bandung penempati posisi perkara tertinggi yang diajukan. Penelitian ini menganalisis mengenai kekerasan dalam rumah tangga yang di proses di Pengadilan Agama, bentuk perlindungan hukum yang di lakukan saat menangani KDRT dalam perundang-undangan dan bentuk perlindungan hukum yang di lakukan di Pengadilan A gama Bandung. Metode pendekatan yang digunakan yang adalah yuridis empiris sosiologis dengan lokasi penelitian di wilayah Pengadilan Agama Bandung. Berdasarkan hasil penelitian, perlindungan hukum kepada korban KDRT bisa dilakukan oleh banyak kalangan, dari advokat, pengadilan, kepolisian, kejaksaan, masyarakat, petugas kesehatan, lembaga sosial. Bentuk perlindungan hukum yang berada di Pengadilan Agama adalah dengan memberikan bantuan hukum dari advokat dan bantuan hukum berupa mengabulkan putusann gugat cerai oleh hakim.